calc question?

Let f(x)=x^7-3x^5+8x^3-2x-3

Then f '(x) is 

f '(5) is

f ' '(x) is

and f ' ' (5) is.

2 Answers

Relevance
  • TomV
    Lv 7
    1 month ago

    f(x) = x⁷ - 3x⁵ + 8x³ - 2x - 3

    f'(x) = 7x⁶ - 15x⁴ + 24x² - 2

    f'(5) = 109375 - 9375 + 600 - 2 = 100598

    f"(x) = 42x⁵ - 60x³ + 48x

    f"(5) = 131250 - 7500 + 240 = 123990

  • 1 month ago

    f(x) = x⁷ – 3x⁵ + 8x³ – 2x – 3

    f'(x) = 7x⁶ – 15x⁴ + 24x² – 2

    f'(5) = 7•5⁶ – 15•5⁴ + 24•5² – 2

    f'(5) = 109375 – 9375 + 600 – 2 = 100598

    f''(x) = 42x⁵ – 60x³ + 48x

    f''(5) = 42•5⁵ – 60•5³ + 48•5

    etc

Still have questions? Get your answers by asking now.